A Model for Residential Building Energy Consumption Characteristics and Energy Demand: A Case in Chongqing. (2015) - Yang, Qiaoxia; Liu, Meng; Huang, Chunyu; Min, Yunran; Zhong, Yiqun
Abstract: This study adopts a bottom-up typical method to establish the microscopic model to simulate the urban residential building energy consumption. The model is composed of a three-hierarchy structure: a) the classification according to the climate; b) according to the energy use; c) according to the energy intensity. Based on the model, energy consumption of urban residential building in Chongqing is calculated as an example. The calculation results of the model and the actual energy consumption are compared and validated. The residential building energy consumption model can be used to analyze the energy consumption in the past years using the existing data, as well as the development trend of the related factors so that the appropriate energy saving measures can be selected properly.